The challenge of film to innovation and entrepreneurship studies. (1st September 2016) - Wood, Martin; Glisovic, Smiljana; Berkeley, Leo
Abstract : This commentary supplements the work of a creative practice research project that generates new ways of thinking about innovation and entrepreneurial processes. Our creative method, underwritten by the logic of sensation and presented in film format, operates as an alternative form of research in these fields, where results are normally conveyed in book or journal paper. Film-based research has developed distinctive qualitative, empirical and theoretical vocabularies that can expand the nature and range of evidence, argument and expression across the broad range of innovation and entrepreneurship studies. 600 Mills, the film that accompanies this paper, is available at https://doi.org/10.1080/08109028.2017.1336011 .